Metabolism of innate immune cells: impact on atherosclerosis. Issue 5 (October 2018) - Riksen, Niels P.; Stienstra, Rinke
Abstract : Purpose of review: It is increasingly recognized that profound metabolic changes occur in activated myeloid cells, which shape their inflammatory phenotype and cellular functions. The purpose of this review is to summarize the accumulating evidence that major metabolic adaptations occur in monocytes and macrophages in the context of atherosclerosis ultimately modulating atherosclerotic plaque formation. Recent findings: Plaque macrophages show a profound metabolic reprogramming which is driven by atherogenic factors in the plaque microenvironment, such as damage associated molecular patterns, modified lipoproteins, and hypoxia. In addition, systemic atherogenic factors modulate metabolism of circulating monocytes and their bone marrow progenitors. Activation of glycolysis, the pentose phosphate pathway, and fatty acid synthesis, a reduction of fatty acid oxidation accompanied by complex changes in the lysosomal handling of lipids all appear to facilitate atherogenesis. These processes also drive the development of trained immunity, a phenomenon describing the persistent pro-inflammatory phenotype that develops after brief stimulation of monocytes with pro-atherogenic stimuli. Summary: A pro-atherosclerotic environment reprograms the metabolism of myeloid cells in the various developmental phases of atherosclerosis. Knowledge of these metabolic programs facilitates the development of novel drugs to prevent atherosclerotic cardiovascular disease.